PENDIDIKAN AGAMA KRISTEN DALAM MEMBANGUN WAWASAN KEBANGSAAN MENGHADAPI ISU INTOLERANSI DAN RADIKALISME - Ramot Peter (Vox Dei: Jurnal Teologi dan Pastoral, 2020)
The issues of intolerance and radicalism have penetrated the dimensions of education in Indonesia. The bad behavior of students that leads to intolerance and radicalism has disturbed the life of the nation. The government is addressing these problems by launching a character education program and a mental revolution movement. These programs and movements have not had a maximum impact so they need to involve the world of education. This research needs to be done to identify students' understanding of the importance of PAK learning in the context of building a national character; find students' understanding in addressing the dangers of radicalism and intolerance; and, providing alternative solutions to form a nationalistic character in preventing intolerance and radicalism. The method used in this research is a qualitative method with a descriptive-analytical approach using various data obtained through interviews and questionnaires as primary and secondary data through books, journals, magazines, newspapers and other relevant sources. After an unstructured interview, counseling was carried out for enrichment and further distribution of questionnaires to students. The research was conducted at the Asih Lestari Jakarta Orphanage on the residents of the orphanage called students of various levels and ages. The results of the questionnaire data collection show that: first, students understand with confidence that PAK learning is very supportive of building national-minded character; second, students are able to express attitudes towards the dangers of intolerance and radicalism; third, the formation of a national-minded character as an effort to support the mental revolution movement and alternative solutions to prevent intolerance and radicalism. Thus, all Christian Education is expected to be able to develop PAK learning as a means of building nationalistic character so that students have a nationalistic attitude to prevent the dangers of intolerance and radicalism.